Перспективний генератор випадкових бітів на геш-функціях та його властивості - Шапочка, Н. В. (ХНУРЭ, 2009)
The requirements to pseudorandom bit generators are proved and determined. The technique is offered and the result of research of statistical characteristics random bit generator on hash function is resulted